Management of the patients with Ebola virus desease - Bondarenko, A; Hvozdetska, M; Zoc, Ya (Annals of Mechnikov's Institute, 2020)
The largest in the history of the Ebola virus disease (EVD) outbreak was recorded in 2014. There are 9976 lethal cases from 24282 infected people (data up to 8 March 2015) within a year from the time of its announcement in West African countries. The outbreak started in Guinea then spread to neighbouring Sierra Leone and Liberia across land borders, to Senegal and Mali by ground transportation, and to Nigeria, Spain, United States of America and the United Kingdom by air transport.If in the previous years disease was the problem of endemic countries in Central Africa nowadays it became a major medical and social problem all over the world. The effective licensed drugs for the treatment and prevention of the disease does not currently exist, experimental drugs (ZMapp, TKM-100802, AVI 7537 Sarepta, Favipiravir T705, BCX4430 Biocryst, Brincidofovir, Nano Silver et al.) are extremely limited, and they are still under investigation.Evidence their effectiveness is suggestive, but not based on solid scientific data from clinical trials. Safety is also unknown. There is consensus that the hyperimmune globulin or convalescent plasma containing high titres of specific neutralizing antibodies to Ebola virus, which leads to decrease the viral load in the blood, is considering to use in an epidemic area as a matter of priority.Experience has shown that the risk of EVD importation into Ukraine remains high despite all preventive measures. Thereby health care providers should be prepared to confront this problem and know how to manage the symptoms of the disease.The management of the patients with EVD mainly should be aimed to early recognition of severe disease and its complications, in combination with appropriate symptomatic therapy. Health care workers should pay careful attention to standard precautions and wear special protective clothing, including goggles, masks and gloves while providing clinical care. Management of intoxication, dehydration, bleeding and shock is a basic and is carried out by common methods.Management of the pain syndrome and anxiety is especially important too.Ribavirin is recommended for the treatment of the patients with Lassa fever and CCHF and it does not apply to the Ebola and Marburg viruses. In most cases, it is impossible to make the diagnosis based only on epidemiological anamnesis and clinical symptoms due to the absence in Ukraine of laboratory express diagnostics kits. Ribavirin should be given empirically to all patients with suspected EVD and other viral haemorrhagic fevers considering difficulties of the differential diagnosis at early stage of infection, especially in pregnant women, due to extremely high maternal and fetal mortality associated with Lassa fever despite on drug adverse effects.All patients should be screened for malaria considering common signs of the EVD clinical manifestations and tropical malaria, antiparasitic therapy should be given to those with a positive result of the research.The intensive supportive care for EVD is the same time for the septic shock due to bacterial infections and malaria. Intensive supportive care is the only clinical management that can be provided to these patients and may have a positive impact on disease outcome. The treatment of the shock should be comprehensive and aimed to maintain vital functions.Broad-spectrum antibiotics should be given empirically during the first hour of the shock therapy. Choice of antibiotics depends on presence of signs of local infection, local disease patterns, and availability of antibiotics. Thus, management of EVD should be based on a set of measures such as clinical management, surveillance and contact tracing, high-quality laboratory services, safe burial and social mobilization.